2010
DOI: 10.1007/s11274-010-0435-2
|View full text |Cite|
|
Sign up to set email alerts
|

A new strain of Bjerkandera sp. production, purification and characterization of versatile peroxidase

Abstract: The lignin modifying enzymes (LMEs) secreted by a new white rot fungus isolated from Chile were studied in this work. This fungus has been identified as a new anamorph of Bjerkandera sp. based on the sequences of the ribosomal DNA and morphological analysis at light microscopy showing hyaline hyphae without clamp connection, cylindrical conidia and lack of sexual forms, similar to those reported in other Bjerkandera anamorphs. The characterization of the culture medium for the highest LMEs production was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 30 publications
(30 reference statements)
2
41
0
Order By: Relevance
“…Figures 5A and 5B, respectively, and were found to be similar in magnitud to those reported by VP produced from Bjerkandera sp. [42] In both cases it was observed that for a given value of Mn 2þ , the reaction rate is independent of its concentration, showing the typical profile of saturation kinetic by substrate. In fact, this can be observed as Mn 2þ presented a strong effect at low concentrations, but from values higher than 250-300 µM a pseudo-saturation region was reached, in which Mn 3þ -tartrate formation was constantly maintained or increasing at a fairly low rate.…”
Section: Enzymatic Kinetic Studymentioning
confidence: 84%
See 2 more Smart Citations
“…Figures 5A and 5B, respectively, and were found to be similar in magnitud to those reported by VP produced from Bjerkandera sp. [42] In both cases it was observed that for a given value of Mn 2þ , the reaction rate is independent of its concentration, showing the typical profile of saturation kinetic by substrate. In fact, this can be observed as Mn 2þ presented a strong effect at low concentrations, but from values higher than 250-300 µM a pseudo-saturation region was reached, in which Mn 3þ -tartrate formation was constantly maintained or increasing at a fairly low rate.…”
Section: Enzymatic Kinetic Studymentioning
confidence: 84%
“…when a medium with high nitrogen concentration was used. [42] On the other hand, SSF of P. eryngii was conducted by using banana peel as growth medium for a total of 28 days of operation. According to the results, presented in Figure 2, consumption rate of reducing sugars from the banana peel was increased gradually until day 18, when the enzyme activity attained its maximum value at approximately 10,800 U L À 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The production of lignolytic enzymes and its regulation has been intensively studied in various lignin degrading fungi (Bonnarme &Jeffries 1990;Hakala et al 2006; Jiménez-Tobon et al 2003;Kamitsuji et al 2004;Lankinen et al 2005; Martínez et al 1996;Moilanen et al 1996;Nuske et al 2002; Perie &Gold 1991;Palma et al 2000;Petruccioli et al 2009;Schneegab et al 1997; Swamy &Ramsay 1999;Steffen et al 2002;Susla et al 2008;Silva et al 2008;Sklenar et al 2010;Singh et al 2011; Taboada-Puig et al 2011;Vares et al 1995;Wang et al 2001;Wang et al 2008) and novel bacterial strains (Bharagava et al 2009; Mishra &Thakur 2010;Yadav et al 2011). Recombinant production has been studied in filamentous fungi (Conesa et al 2000;Irie et al 2001;Li et al 2001;Mayfield et al 1994;Stewart et al 1996), yeasts (Jiang et al 2008a), bacterial (Whitwam &Tien 1996) and insect (Johnson et al 1992 ; Pease et al 1991) hosts with successful production but modest yields of active enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…Otherwise, in order to maximize peroxidase activity, lactose has already been identified as a good carbon source for Bierkandera spp. when the nitrogen source was organic [43], as in SLM and SDM media. P. crysosporium was found to be surprisingly less active than B. adusta in lignin removal effectiveness in all three growth conditions (Figure 2b).…”
Section: Lignin Removal Efficiency On Synthetic Pulp-and-paper Mill Wmentioning
confidence: 99%